1988
DOI: 10.1177/088506668800300204
|View full text |Cite
|
Sign up to set email alerts
|

Management of Renal Complications of Liver Disease

Abstract: Included among the most important renal complica tions of liver disease is progressive sodium retention leading to the formation of edema and ascites and the hepatorenal syndrome (HRS). When ascites is refractory to conventional treatment, the use of invasive proce dures such as reinfusion or dialytic ultrafiltration of as cites or the peritoneovenous shunt may be indicated. The possibility that continuous arteriovenous hemo filtration may be useful in removing fluid in patients who would not otherwise tolerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
(61 reference statements)
1
3
0
Order By: Relevance
“…Impaired renal perfusion plays a key role in sodium and fluid retention and severe renal vasoconstriction leads to the development of hepatorenal syndrome 1,2,4 . In the present study, sodium excretion was found to be decreased in decompensated cirrhotic patients, especially in ascitic patients.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…Impaired renal perfusion plays a key role in sodium and fluid retention and severe renal vasoconstriction leads to the development of hepatorenal syndrome 1,2,4 . In the present study, sodium excretion was found to be decreased in decompensated cirrhotic patients, especially in ascitic patients.…”
Section: Discussionsupporting
confidence: 51%
“…The RRI were correlated with the severity of hepatocellular dysfunction, assessed by C‐P score. The RRI, study by means of Doppler USG, showed progressively increased concentrations with the evolution of the liver disease, probably with deterioration of the renal vascular hemodynamics and with the activation of endogenous compensatory mechanisms due to decrease of the effective plasma volume 1 . Numerous adult studies showed that kidney dysfunction characterized by early renal hemodynamic changes before clinically recognized kidney disease might commonly develop in patients with established liver disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations